PEDAGOGICAL INFLUENCE FACTORS OF INDEPENDENT MASTERING OF BIOLOGY LESSONS BY STUDENTS (International journal of artificial intelligence, 2025)
In this article, the pedagogical influence factors of students' independent learning of Biology lessons, the stages of the student's own independent experience, the skills and qualifications of the student according to each subject program, as well as the sources of independent learning, Pedagogical possibilities of deep understanding and systematization, logical thinking, application of independently acquired knowledge based on moral values, formation of effective independent work skills are highlighted.